Children's spirituality: Exploring spirituality in the lives of cancer survivors and a healthy comparison group. (June 2020) - Moore, Kelsey; Talwar, Victoria; Gomez-Garibello, Carlos; Bosacki, Sandra; Moxley-Haegert, Linda
This study found that children with a history of cancer had higher scores on certain measures of spirituality compared to their healthy peers. Health history was found to significantly moderate the relations among spirituality and outcome variables, such as depression and anxiety. Furthermore, parent–child dyadscancer had more highly correlated scores than parent–child dyadshealthy on both the Depression subscale and the Existential Well-Being subscale, whereas parent–child dyadshealthy had more highly correlated scores than parent–child dyadscancer on the Duality factor. Limitations and future directions are discussed.